Magnetic resonance imaging of the hand joints in patients with inflammatory bowel disease and arthralgia: a pilot study. (October 2014) - Brakenhoff, LKPM; Stomp, W; van Gaalen, FA; Hommes, DW; Bloem, JL; van der Heijde, DMFM; Fidder, HH; Reijnierse, M
<x xml:space="preserve">Abstract</x> Objectives: To assess whether subclinical inflammatory changes are present on magnetic resonance imaging (MRI) in patients with inflammatory bowel disease (IBD) and arthralgia. Method: In this pilot study, painful hand joints [metacarpophalangeal (MCP), proximal interphalangeal (PIP), and/or distal interphalangeal (DIP)] of 11 IBD patients (age 18–45 years) with continuous pain for > 6 weeks were scanned on a 1.5-T extremity MRI system. A control group of 11 IBD patients without joint pain who were matched for type and disease duration of IBD, gender, and age was included. All patients were clinically examined by a rheumatologist for the presence of pain and arthritis. Imaging was performed according to a standard arthritis protocol with intravenous contrast administration on the same day. Images (blinded for clinical information) were evaluated by two readers in consensus for the presence of joint fluid, synovitis, tenosynovitis, enthesitis, erosions, cartilage defects, and bone marrow oedema. Results: Enthesitis was seen in three hand joints (MCP 2, MCP 3, PIP 3) of 2/11 (18%) arthralgia patients and in none of the control group (p = 0.48). A small amount of subchondral bone marrow oedema was seen in the metacarpal head of two controls. No other abnormalities were observed. Conclusions: Several young IBD patients with chronic hand pain had subclinical inflammation on MRI, which invites for further study in a larger group of patients.